User Interface Design of a Web- and Mobile-Based Sales Information System for GBL Chicken Modayag MSME - Tamuntuan, Virginia; Mamangki, Hamdi; Tuntun, Ritham (PT. GWEX NET PUBLISHER, 2025)
GBL Chicken Modayag is a micro-scale culinary business that still relies on manual transaction recording and has not optimally utilized digital media for sales and marketing activities. This condition leads to a high risk of data loss, limited promotional reach, and ineffective dissemination of menu and promotional information to customers. This study aims to design a web and mobile-based sales information system interface as a digital solution to these problems. The research method includes direct observation and interviews with the business owner to analyze the existing system, followed by the design of a proposed system using flowcharts, Entity Relationship Diagrams (ERD), and user interface design developed with Figma. The results of this study produce a sales information system design that supports menu management, online and offline ordering, transaction processing, sales reporting, and communication through a chat feature involving multiple user roles, namely admin, cashier, courier, and customer. The proposed system design is expected to improve sales management efficiency, reduce the risk of transaction data loss, and expand the marketing reach of MSMEs through web and mobile-based digital platforms. However, this study is limited to the design stage and does not include system implementation or usability evaluation, so the results serve as a conceptual reference for future development and testing.